2016
DOI: 10.1002/acn3.293
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient disease inhibition by intrathecal rituximab in progressive multiple sclerosis

Abstract: ObjectiveInaccessibility of the inflammation compartmentalized to the central nervous system (CNS) may underlie the lack of efficacy of immunomodulatory treatments in progressive multiple sclerosis (MS). The double blind combination of Rituximab by IntraVenous and IntraThecAl injection versus placebo in patients with Low‐Inflammatory SEcondary progressive MS (RIVITALISE; NCT01212094) trial was designed to answer: (1) Whether an induction dose of intravenous and intrathecal rituximab efficiently depletes CNS B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
146
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 137 publications
(152 citation statements)
references
References 34 publications
2
146
1
3
Order By: Relevance
“…The current study demonstrates that approximately 0.1% of systemically administered daclizumab reaches the intrathecal compartment, consistent with other monoclonal antibodies such as rituximab 17, 18. The observed rise in serum and CSF IL‐2 levels provides evidence for the ability of daclizumab to inhibit consumption of IL‐2 by activated T cells14 in both systemic and intrathecal compartments.…”
Section: Discussionsupporting
confidence: 83%
“…The current study demonstrates that approximately 0.1% of systemically administered daclizumab reaches the intrathecal compartment, consistent with other monoclonal antibodies such as rituximab 17, 18. The observed rise in serum and CSF IL‐2 levels provides evidence for the ability of daclizumab to inhibit consumption of IL‐2 by activated T cells14 in both systemic and intrathecal compartments.…”
Section: Discussionsupporting
confidence: 83%
“…The authors demonstrated that higher rituximab concentrations paradoxically decreased the rituximab concentration on the surface of B cells, due to facilitated internalization of CD20/ rituximab complexes in vitro [Komori et al 2016]. Therefore, the 200 mg dose was considered sufficient to saturate CD20 leading to long-lasting depletion of B cells from peripheral circulation [Komori et al 2016]. However, greater surface binding does not mean more-efficient depletion and the study did not investigate B-cell depletion in vivo for the different rituximab dosages to allow definite conclusions.…”
Section: Dosing Of B-cell-depleting Therapies: Experiences From Rituxmentioning
confidence: 99%
“…rituximab on day 1 and day 15 with intrathecally administered rituximab. The authors demonstrated that higher rituximab concentrations paradoxically decreased the rituximab concentration on the surface of B cells, due to facilitated internalization of CD20/ rituximab complexes in vitro [Komori et al 2016]. Therefore, the 200 mg dose was considered sufficient to saturate CD20 leading to long-lasting depletion of B cells from peripheral circulation [Komori et al 2016].…”
Section: Dosing Of B-cell-depleting Therapies: Experiences From Rituxmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients using rituximab for other indications, PML cases have rarely been reported [70]. Although rituximab rapidly and consistently decreases the numbers of peripheral CD20+ and CD19+ cells [71], a small phase II trial of intrathecal rituximab was terminated early because of low efficacy on the CSF biomarkers [72]. Rituximab induced an incomplete and transient depletion of B cells in the CSF, whilst the effects on peripheral B cells were complete and lasting.…”
Section: Agents In Trialmentioning
confidence: 99%